- 1Using the quadratic equation x2-4x-5=0, perform the following tasks by A)Solve b
Using the quadratic equation x2-4x-5=0, perform the following tasks by A)Solve by factoring and show workb) solve by using the quadratic formula

- 2place the following equations in the standard form of a quadratic equation, ax^2+bx+c=0
a)4/x^2+3/x-10=0
b)6+4/x-1=5/x-3
c)3.5x+4.6/x=1.2
use the quadratic formula to solve these quadratic equations
a)3x^2+2x-8=0
b)5x^2+7x=12
place the following equations in the standard form of a quadratic equation, ax^2+bx+c=0 a)4/x^2+3/x-10=0 b)6+4/x-1=5/x-3 c)3.5x+4.6/x=1.2 use the quadratic formula to solve these quadratic equations a)3x^2+2x-8=0 b)5x^2+7x=12

- 3Solve the quadratic equation 2x to the 2nd power -3x-2=0using the quadratic formula
Solve the quadratic equation 2x to the 2nd power -3x-2=0using the quadratic formula. Read the information in the assignment list to learn more about how to type math symbols in MS Word, such as the square root.

- 4solve this quadratic equation by using the quadratic formula... 3xsquared+7x-6=0
solve this quadratic equation by using the quadratic formula... 3xsquared+7x-6=0

- 5solve the quadratic equation by factoring then by using the quadratic formula
a2+6a+8=0
s2-9s+8=0
3y2+6y-24=0
solve the quadratic equation by factoring then by using the quadratic formula a2+6a+8=0 s2-9s+8=0 3y2+6y-24=0

- 6solve the quadratic equation 6x^2 +3x -18=0 using the quadratic formula
solve the quadratic equation 6x^2 +3x -18=0 using the quadratic formula.

- 7Use the quadratic formula to solve the following quadratic equation
Use the quadratic formula to solve the following quadratic equation. __ 4x^2+ 5x = 6

- 8Use the quadratic formula to solve the following quadratic equation
x^2- 4x+ 2 =0
Use the quadratic formula to solve the following quadratic equation x^2- 4x+ 2 =0

- 9Solve the quadratic equation using the Quadratic Formula:
2y^2-y=6
Solve the quadratic equation using the Quadratic Formula: 2y^2-y=6

- 10Solve this quadratic equation using the quadratic formula
Solve this quadratic equation using the quadratic formula. x2 - 6x + 6 = 0 2x2 - 2x = 1 3x2 + 5x + 1 = 0

- 11Solve the quadratic equation using the Quadratic Formula:
3x^2-2x-2=0
Solve the quadratic equation using the Quadratic Formula: 3x^2-2x-2=0

- 12How do I solve this 2y^2-y=6 quadratic equation using the Quadratic Formula
How do I solve this 2y^2-y=6 quadratic equation using the Quadratic Formula.